NIR -I and NIR-II irradiation tumor ablation using NbS2 nanosheets as the photothermal agent. Issue 43 (1st November 2021) - Sun, Songqiang; Song, Yapai; Chen, Jiabo; Huo, Minfeng; Chen, Yu; Sun, Lining
Abstract : The NbS2 -PVP nanosheets exhibit excellent tumor cell ablation mediated by 1064 nm or 808 nm laser after intravenous injection in mice. Abstract : Photothermal therapy has been considered a powerful means of cancer therapy due to its minimal invasiveness, effectiveness, and convenience. Although promising, the therapeutic effects are greatly limited as they rely on the photothermal agent (PTA). It is urgent to develop new PTAs with high photothermal conversion performance, especially under irradiation in the long-wavelength biowindows. Herein, a dual-biowindow-responsive PTA made of NbS2 -PVP nanosheets was fabricated to be used both in the first near-infrared (NIR-I) and the second near-infrared (NIR-II) biowindows. With excellent hydrophilicity and biocompatibility, the nanosheets could effectively convert the near-infrared (NIR) light into heat, showing prominent photothermal stability. The calculated photothermal conversion efficiencies reached 59.2% (under NIR-I excitation) and 69.1% (under NIR-II excitation), respectively, which are comparable to those of metallic PTAs. The NbS2 -PVP nanosheets had low cytotoxicity and could trigger strong photothermal treatment and cause cancer cell death upon irradiation by NIR-I or NIR-II light in vitro . Moreover, we have also demonstrated the highly efficient tissue ablation and tumor inhibition capability of NbS2 -PVP nanosheets in vivo . This work explores an effective PTA of two-dimensional nanomaterials in NIR-I and NIR-II biowindows and offers a reference for the design of new kinds of PTAs.